2020
DOI: 10.1155/2020/6028747
|View full text |Cite
|
Sign up to set email alerts
|

Low Stroke Volume Index in Healthy Young Men Is Associated with the Incidence of Acute Mountain Sickness after an Ascent by Airplane: A Case‐Control Study

Abstract: Background. The aims of this study were to explore the characteristics of left ventricular (LV) functional changes in subjects with or without acute mountain sickness (AMS) and their associations with AMS incidence. Methods. A total of 589 healthy men were enrolled and took a trip from Chengdu (500 m, above sea level (asl)) to Lhasa (3700 m, asl) by airplane. Basic characteristics, physiological data, and echocardiographic parameters were collected both at Chengdu and Lhasa, respectively. AMS was identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…In a new relatively large-scale case-control study it was revealed that the decrease in stroke volume index correlated with the altered left ventricular filling pattern was related to the onset and severity of AMS [ 44 ].…”
Section: Physiology and Pathophysiology In Healthy At High Altitudementioning
confidence: 99%
“…In a new relatively large-scale case-control study it was revealed that the decrease in stroke volume index correlated with the altered left ventricular filling pattern was related to the onset and severity of AMS [ 44 ].…”
Section: Physiology and Pathophysiology In Healthy At High Altitudementioning
confidence: 99%
“…Independent risk factors for AMS, such as genetics, sex, body mass index (BMI), and the ascending altitude and velocity, have been confirmed in previous studies (Santantonio et al, 2014;Luks et al, 2017). Moreover, previous findings have also demonstrated that AMS may be affected by the baseline and HA-induced changes of cardiovascular indices (Lanfranchi et al, 2005;Hamm et al, 2020;Ke et al, 2020). However, conflicting results are often reported and the exact mechanism of AMS still needs to be fully elucidated.…”
Section: Introductionmentioning
confidence: 76%
“…However, the characteristics of LV functionrelated responses in AMS patients have not been illustrated so far. Our previous reports have documented the cardiac adaptations in patients with AMS compared with healthy subjects (Ke et al, 2020). AMS patients had higher HR but lower EDV, stroke volume, and E/A ratio than AMS-free subjects.…”
Section: Cardiac Response After Ha Exposure In Ams Subjectsmentioning
confidence: 91%
“…Some maladaptive individuals may suffer acute mountain sickness (AMS), which is characterized by headache and other related symptoms ( 3 , 4 ). Previous studies have indicated that certain cardiovascular system indicators including electrocardiogram changes and cardiac systolic function are related to the occurrence and development of AMS ( 5 , 6 ). Moreover, excessive elevation of arterial BP is detrimental to the body and is considered to be closely associated with AMS ( 7 ).…”
Section: Introductionmentioning
confidence: 99%